Hand Rearing of Giraffe Calves at Sri Chamarajendra Zoological Gardens , Mysore - Khadri, S. S. M. S.; Valandikar, S. C. (Indian Forester, 2002)
Successful hand-rearing of four giraffe calves at Shri Chamarajendra Zoological Garden , Mysore was done with feeding of calves with cow colostrum (lOOOml) on the 1st day every 3 hrs to 3rd day for 3 days and 50% of whole cow milk (500ml) and 50% of colostrum (500ml) next 72 hours. Further 3 days with 75% of colostrum and 25% of whole cow milk up to 1200 ml was given. Giving increment of 300 ml up to 3rd month and further increase up 100 ml up to 6th month was practiced. From 7th month onwards , 100ml cow milk was reduced every month up to 9th month. The calf was weaned at this stage. Browsing was practiced from 20th day onwards with Acacia leaves , fresh grass , Ficus , Neem and Jamun leaves. Concentrate was given at 4th month onwards. Daily feeding of cow milk 6 times a day continued up to 5th month. From 6th month onwards 5 feeds of cow milk a day , on 7th month 4 feeds of cow milk a day were done. On 8th month , 3 feeds of cow milk a day , 9th month 2 feeds a day for a month and then discontinued. The calf was then left to feed with fellow brothers and parents to graze and browse in the enclosure. Supplementation of Vitamins , minerals started from 3rd week onwards.